French school of direct sound: Jean-Pierre Ruh and Éric Rohmer (Significação: Journal of Audiovisual Culture, 2022)
The article focuses on one of the most prominent representatives of the French direct sound school, the technician Jean-Pierre Ruh, from his work with the filmmaker Éric Rohmer in the films Ma nuit chez Maud (My night at Maud’s, 1969), Le genou de Claire (Claire’s knee, 1970) and L’amour l’après-midi (Chloe in the afternoon, 1972). Based on testimonies by Jean-Pierre Ruh himself, we intend to focus on key issues for the direct sound school, especially with regard to the exploration of the off-screen sounds, sound imperfections, and the ordinary sounds, understood within a conception that values a truth and a singularity of the sound in the film. We observed that each movie has its own particularity and its unique sound, and all of them explore the voices projected into the space, open or closed, which adds a perspective and depth information.